Computer supported cooperative work and social computing : 13th CCF Conference, ChineseCSCW 2018, Guilin, China, August 18-19, 2018, Revised Selected Papers /: 13th CCF Conference, ChineseCSCW 2018, Guilin, China, August 18-19, 2018, Revised Selected Papers. ([2019]) - Unknown
No abstract available